Dynamics of Clean and Sustainable Households’ Energy Technologies in Developing Countries: The Case of Improved Cookstoves in Ghana - Abdulai Adams; Emmanuel Tetteh Jumpah; Hamidatu S. Dramani (Sustainable Futures, 2023)
Access to clean energy for efficient cooking remains a challenge to most households both in rural and urban settings. Government and stakeholders in the clean energy sector have been making efforts to increase the availability and accessibility to clean energy technologies for cooking. This study aims to analyse the determinants and constraints associated with the adoption of improved cooking stoves (ICS) in Ghana using a sample of 194 respondents purposively selected. By applying the logistic regression and non-parametric models, the study revealed that household size, education of the household head, availability of stoves and the intensity/ frequency of use impact adoption decisions. Furthermore, affordability, low level of awareness, accessibility, and poor quality of stoves are the ranked constraints hindering the widespread adoption of ICS. These findings have implications for consumers, stove manufacturers, financiers, promoters and the government. Strategies aimed at improving stove quality and promotional activities including training and public awareness through the media and public fora need to be vigorously pursued by stakeholders to ensure energy for all.